2023
DOI: 10.3390/ijerph20021400
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition from Large-Scale Video Clips with Cross-Attention and Hybrid Feature Weighting Neural Networks

Abstract: The emotion of humans is an important indicator or reflection of their mental states, e.g., satisfaction or stress, and recognizing or detecting emotion from different media is essential to perform sequence analysis or for certain applications, e.g., mental health assessments, job stress level estimation, and tourist satisfaction assessments. Emotion recognition based on computer vision techniques, as an important method of detecting emotion from visual media (e.g., images or videos) of human behaviors with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Wu et al [62] May 2019 EMOTIC Zhang et al [63] August 2019 EMOTIC Mittal et al [56] June 2020 EMOTIC Thuseethan et al [64] September 2021 EMOTIC Peng et al [65] December 2021 EMOTIC Wu et al [66] August 2022 EMOTIC Yang et al [67] October 2022 EMOTIC Lee et al [17] October 2019 CAER Lee et al [17] October 2019 CAER-S Gao et al [68] January 2021 CAER-S Zhao et al [69] May 2021 CAER-S Zhao et al [70] July 2021 CAER-S Le et al [18] December 2021 CAER-S Le et al [18] December 2021 NCAER-S 1 Wu et al [66] August 2022 CAER-S Chen et al [20] October 2022 CAER-S Costa et al [19] October 2022 CAER-S Zhou et al [71] January 2023 CAER-S…”
Section: Approach Available From Datasetmentioning
confidence: 99%
“…Wu et al [62] May 2019 EMOTIC Zhang et al [63] August 2019 EMOTIC Mittal et al [56] June 2020 EMOTIC Thuseethan et al [64] September 2021 EMOTIC Peng et al [65] December 2021 EMOTIC Wu et al [66] August 2022 EMOTIC Yang et al [67] October 2022 EMOTIC Lee et al [17] October 2019 CAER Lee et al [17] October 2019 CAER-S Gao et al [68] January 2021 CAER-S Zhao et al [69] May 2021 CAER-S Zhao et al [70] July 2021 CAER-S Le et al [18] December 2021 CAER-S Le et al [18] December 2021 NCAER-S 1 Wu et al [66] August 2022 CAER-S Chen et al [20] October 2022 CAER-S Costa et al [19] October 2022 CAER-S Zhou et al [71] January 2023 CAER-S…”
Section: Approach Available From Datasetmentioning
confidence: 99%
“…Instead of that when machine learning is used for stress detection the results are entirely different. Multiple studies (Li and Liu 2020;Mittal et al 2022;Zhou et al 2023;Liu et al 2023) have shown that with intervention of machine learning, stress detection took a new reform by getting a higher prediction accuracy in less and reallife scenario transforming lives of many.…”
Section: Introductionmentioning
confidence: 99%
“…Automatic emotion recognition is expected to be an effective technology for effortless communication and forms a major research hotspot in the field of artificial intelligence. Emotions can be identified from various sources of information, such as speech (voice), utterance transcript, facial expressions, and brain waves [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Among these sources, speech can be used for emotion recognition in face-to-face mode as well as in remote communication via telephone or video calls.…”
Section: Introductionmentioning
confidence: 99%